A Case Study on Kencana Specialist Hospital - Suhaimi, Mazlina (1997)
KENCANA Specialist Hospital located in the center of Kuala Lumpur was a single-discipline hospital that had 275 beds and ran 12 clinic sessions per day for 5 days with total patients of 250 per day. The hospital was established on 1 September 1992 and had 16,000 active patients from all over Malaysia inclusive foreigners. It was headed by a Chief Executive Officer, Dr. Norazah, and there were 3 major divisions under her which were Medical, Administration and Finance. The divisions were managed by the respective Senior Managers and under them there were various departments and units. The hospital operating revenue stood at a stable RM80.32 million in 1995/96 financial year. There was an increase of less than 1% compared to the operating revenue of RM79.58 million achieved in the previous financial year. A total of 58,523 patients sought treatment at the hospital in 1995/96, an increase of 10% compared to the 1994/95 figure. Out of these, 8,081 were inpatients and 50,442 were outpatients. KENCANA's outpatient and inpatient workload from 1992 to 1997 is illustrated in Appendix I. KENCANA Specialist Hospital manpower costs increased by 1 0% from RM24.16 million in 1994/95 to RM26.47 million in 1995/96. The hospital's manpower strength was 571 as compared to 4 25 during its first year of operation. Being a service organization, KENCANA emphasized strongly on training and development of its human resources. Members of the staff were given opportunities to attend external courses, seminars and conferences both at home and abroad to improve their knowledge and skills.